Development and Validation of an Augmented Reality–Supported Contextual Teaching and Learning Module for Projectile Motion - Yusuf Axmed; Sahra Warsame; Asha S. Abshir (International Journal of Education and Learning Studies, 2026)
This study developed and validated a contextualized physics module integrating Augmented Reality (AR) for teaching projectile motion, addressing challenges related to abstract concepts and limited laboratory resources in physics classrooms. The research employed a Design and Development approach using the ADDIE model to produce a learning module that incorporates culturally relevant examples and interactive three-dimensional visualizations accessible through smartphones. The product was evaluated through expert validation and preliminary user testing. Validation by five experts resulted in very high ratings across all assessed aspects, with contextual relevance receiving the highest score (M = 4.75/5.00). Preliminary implementation involving 35 students indicated high levels of perceived practicality and user acceptance, particularly regarding engagement (M = 4.78) and the perceived usefulness of AR visualizations for clarifying projectile motion concepts (M = 4.62). Observational notes during implementation suggested that students actively related the AR simulations to real-world situations presented in the module. These findings indicate that the developed module demonstrates strong validity and practical feasibility as a technology-supported instructional resource that integrates Augmented Reality with Contextual Teaching and Learning principles. However, the study focuses on product quality evaluation through expert judgment and student perceptions; it does not measure learning effectiveness or learning gains. Future research may therefore investigate the instructional impact of the module through experimental or quasi-experimental designs.